Er:YAG Laser Assisted Treatment of Central Odontogenic Fibroma of the Mandible - Luis Silva Monteiro; Marco Martins; José Júlio Pacheco; Filomena Salazar; João Magalhães; Paolo Vescovi; Marco Meleti (Case Reports in Dentistry)
Central odontogenic fibroma is a very rare benign odontogenic tumour characterized by a fibrous mature stroma with variable strands or islands of inactive-looking odontogenic epithelium. Our aim is to report a case of a central odontogenic fibroma and describe the clinical usefulness of Er:YAG laser for the surgical treatment of this tumour. A 74-year-old woman presented with an expansive lesion located in a mandible with multilocular and mixed radiographic appearance. A conservative excision using Er:YAG laser was performed. Complete removal was obtained. There were no postoperative complications. The histopatologic features were consistent with the diagnosis of central odontogenic fibroma of rich-epithelium type. No recurrence was observed during follow-up.